KELAYAKAN TEHNIK BUDIDAYA PADI SAWAH MENGGUNAKAN âTEKNOLOGI TAIWANâ DALAM UPAYA PENINGKATAN PRODUKSI. - Supriadi, Herman (Indonesian Journal of Socio Economics)
Â Study on development of âTaiwan Technologyâ in order to increase rice production have been conducted at Riau province during May 2007. The aim of the study was to know the specification, the farmers response, the potential for the increase in the productivity, the regional governments response, the supporting infrastructure and the technical, social-economical feasibility of âTaiwan technologyâ, that lately will be developed widely by the regional government in Riau. The study was carried out in the regency of Rokan Hilir and Kampar that developed this technology.Results of the study showed that the application of this technology could increase the productivity of rice up to 1.6 ton unhusked rice/hectare and increase Â the income around Rp 1.573 million/ season/hectare. The efficiency of both cultural practices (existing and Taiwan technology) almost the same ( B/C ratio around 1) and marginal benefit cost ratio (MBCR = 2,0) showed that adoption of Taiwan technology was profitable. Unfortunatelly not all of the farmer gave a good response to apply this introduce technology, the reason because the technoloty Â needed high input , the pesticide suggestion was also intensive, that it was worried about will cause the impact negaif towards the environment. The reality, not all of the farmers wanted to adopt new technology, and the adopter farmer not fully adopted technology introduced. The technological component that often was adopted widely by the farmer and was continuous was technical the submersion of the seed with salt to select the vigor seed. With the treatment of the submersion to throw the empty or not better seed away, could increase the viability of the seed almost 100%.Hope fully the local government have a good policy to adopt all of good things of this technology and not brought the bad impact for the environment.